2006
DOI: 10.2353/ajpath.2006.050314
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Role of B Cells in Anti-CD40-Induced Necroinflammatory Liver Disease

Abstract: Activated B cells function in antibody production and antigen presentation, but whether they perform any pathophysiological functions at sites of inflammation is not fully understood. Here, we report that intravenous injection of an agonistic anti-CD40 monoclonal antibody (alphaCD40) causes a biphasic inflammatory liver disease in inbred mice. The late phase of disease was suppressed in B-cell-deficient mice and by the depletion of macrophages, but not T cells or natural killer cells. We also report that SCID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…This is consistent with studies by Joyce et al, which first demonstrated the exclusive binding capability of RGR-FITC molecules to angiogenic vessels in RIP-Tag tumors (4). Moreover, compared with unconjugated compounds, anti-CD40-RGR/IL-2-RGR treatment induced limited liver toxicity, as assessed by serum alanine aminotransferase and serum TNF-α ( Figure 1, E and F) (21) and reduced systemic immune responses ( Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI33201DS1). Our data thus demonstrate that vascular targeting is a viable approach to deliver immune-modulating, and otherwise systemically toxic, agents into tumors, which are not accessible by direct intratumoral injections.…”
Section: Peptide-mediated Homing Of Immune Stimulatory Agents Into Sosupporting
confidence: 79%
“…This is consistent with studies by Joyce et al, which first demonstrated the exclusive binding capability of RGR-FITC molecules to angiogenic vessels in RIP-Tag tumors (4). Moreover, compared with unconjugated compounds, anti-CD40-RGR/IL-2-RGR treatment induced limited liver toxicity, as assessed by serum alanine aminotransferase and serum TNF-α ( Figure 1, E and F) (21) and reduced systemic immune responses ( Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI33201DS1). Our data thus demonstrate that vascular targeting is a viable approach to deliver immune-modulating, and otherwise systemically toxic, agents into tumors, which are not accessible by direct intratumoral injections.…”
Section: Peptide-mediated Homing Of Immune Stimulatory Agents Into Sosupporting
confidence: 79%
“…Inflammation and hypertrophy of lymphoid tissues follow, characterized by loss of normal follicular structure and co-localization of activated T cells and B cells in lymphocytic clusters (Peters et al, 2009). Pronounced infiltrates of B cells, NK cells, CD4 + T-cells, dendritic cells and macrophages occur in various organs, mainly the liver but also lung, pancreas and gastrointestinal tract (Kimura et al, 2006;Zhou et al, 2005). Furthermore, lymphadenopathy and splenomegaly occur due to myeloid cell hyperplasia and B-cell expansion.…”
Section: Including Tumor Necrosis Factor (Tnf) Interleukin-(il-) Il-mentioning
confidence: 99%
“…Several human 2,4 and animal [24][25][26][27] studies using CD40 agonists report elevated levels of circulating hepatocyte enzymes ALT and AST, indicative of liver damage. To examine the severity of hepatocellular damage with monotherapy versus combination therapy, we measured plasma levels of ALT and AST in mice after vaccination ( Figure 5A,B).…”
Section: ␣Cd40-induced Hepatocellular Injury Is Reduced By Coadministmentioning
confidence: 99%